The Prophecy of Justice in Micah and Post-Violence Reconciliation: A Biblical-Pastoral Roadmap for the Indonesian Church - Silaen, Jeki (Cattleya Darmaya Fortuna, 2024)
The Book of Micah presents the face of God who stands for justice and rejects all forms of social, economic, and political oppression. In the context of the Indonesian nation still bearing the social wounds of historical violence and injustice, Micah's prophetic message presents a relevant and urgent prophetic voice. This study aims to explore the meaning of the prophecy of justice in the Book of Micah and to formulate a biblical-pastoral roadmap for the Indonesian church in the post-violence reconciliation process. The study was conducted using a theological hermeneutic approach and contextual pastoral reflection, combining the study of biblical texts with the concrete experiences of the Indonesian people. Theologically, Micah presents a vision of God that demands social justice as a manifestation of true faith. The call to “do justice, love mercy, and walk humbly with God” (Micah 6:8) serves as an ethical and spiritual foundation for the church seeking to build a peaceful society. In the post-violence context, this message is not merely moral but also prophetic—demanding structural repentance and the renewal of social systems that perpetuate suffering. Thus, Micah's prophetic theology can form the basis for reconciliation practices that balance justice and forgiveness. This research demonstrates that true reconciliation cannot be separated from acknowledging the suffering of victims and the responsibility of perpetrators. The Indonesian Church, in its pastoral role, is called to be a space of recognition, healing, and social transformation. Micah's prophecy affirms that true peace is not the result of political compromise, but rather the fruit of justice upheld with love. The church needs to live out its prophetic role by speaking up for the voiceless and upholding the values ​​of God's love that transcend ethnic, religious, and ideological boundaries. Furthermore, this research underscores the importance of a biblical-pastoral approach in building a healthy collective memory in post-violence societies. Through transformative biblical and liturgical study, the church can help people reinterpret traumatic experiences in the light of God's love. In this regard, Micah is not only a prophet of the past but also a dialogue partner for the church today in upholding justice and reconciliation. By reading Micah contextually, the church can develop a theology of peace rooted in biblical narratives and relevant to the Indonesian context. The findings of this study are expected to contribute to the development of a contextual theology of peace in Indonesia, particularly in formulating concrete pastoral measures for communities affected by violence. The church is invited not to be merely a spectator in social processes, but to become an agent of renewal that affirms communal life. Following Micah's example, the church is called to speak out for justice for the marginalized.witness to God's healing love and bring about reconciliation based on truth. Thus, Micah's prophecy serves as an inspiration and spiritual roadmap for the Indonesian church to build a peaceful, just, and hopeful society.